Implementation of a competent approach to the education of students of the faculty of pharmacy on external form of studies in the discipline "biophysics and physical methods of analysis" - Ivanchenko, E. Z.; Melnikova, O. Z.; Malakhova, S. N.; Іванченко, Олена Зенонівна; Мельнікова, Оксана Зенонівна; Малахова, Світлана Миколаївна (Sofia : Publishing House "ACCENT", 2020, 2020)
Annotation. The article considers the specifics of the organization of the educational process with the extramural students of the Faculty of Pharmacy during the study of the discipline "Biophysics and Physical Methods of Analysis" in the context of the implementation of a competent approach to learning.
Keywords: the extramural students; competent approach to learning